Effect of volitional preemptive abdominal contraction on superficial multifidus response in healthy subjects during unipodal lower extremity reach task. - Garcia, Luciano; Drusch, Alex; Hooper, Troy; Yang, Hyung Suk; Kublawi, Marwan; Brismée, Jean-Michel; Sizer, Phil (Journal of Bodywork & Movement Therapies, 2025)
To determine the effect of volitional preemptive abdominal contraction (VPAC) on abdominal and superficial multifidus (sMf) activation in healthy subjects during a lower extremity (LE) unipodal functional task. Within-subjects, repeated measure cohort design. Clinical laboratory setting. 30 healthy adults (18 female/12 male), age 20−41 years (26.4 ± 5.1 years), height (170.0 ± 8.5 cm), weight (71.0 ± 14.5 kg) and body mass index (25.0 ± 4.3 kg/m2). The Y-balance test (YBT) on the dominant LE in anterior (ANT), posteromedial (PM), and posterolateral (PL) directions during No-VPAC, abdominal bracing maneuver (ABM), and abdominal drawing-in maneuver (ADIM) conditions. Superficial Mf (sMf), internal oblique (IO), and external oblique (EO) activity measured by surface electromyography. One-way Analysis of Variance (ANOVA) based on 2 (EO/IO) × 3 (VPAC Strategy) design revealed a significant VPAC strategy main effect for IO and EO amplitudes in all directions (p <.05). Post-hoc tests indicated that ABM and ADIM produced significantly greater abdominal contraction relative to No-VPAC. Findings yielded by repeated measures 2 (sMf side) × 3 (VPAC) ANOVAs indicate a significant interaction in PM (p =.002) and PL (p =.003) directions, with greater activation on stance-side sMf established via post-hoc comparisons (p <.001). Pearson correlation analyses failed to uncover any relationships between sMf activation and reach distances. Performing VPAC produces abdominal and stance-side sMf co-activation during PM and PL directed YBT performance. These outcomes give credence to the supportive role of abdominal-multifidus co-activation during unipodal functional reaching activities. • Abdominal co-contraction was able to be produced during the Y-Balance Test. • Lumbar multifidus activation increased with a mild or strong abdominal contraction. • Stance side multifidus activation increased in posterior directions only. • Abdominal contraction did not increase reach distances during the Y-Balance Test.